SHIPYARD PRODUCTIVITY COMPARTMENT AT THE SUPERIOR CLIFFS OF THE MERANTI ISLANDS DISTRICT - Christia Dharma Putra Capah; Nofrizal Nofrizal; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe shipyard was a site either on land or in water generally used for boat building or for boat repair and maintenance. The purpose of this study is compare the similarities and differences between the shipyard productivity that are sample of the research objects located at the Meranti Islands high Cliffs District. The method used in this study was the methods of surveying by direct observation and observation of some shipyards that were on the site using structured interview techniques. Precursor manufacturing dock CV. PRIZAL with the production of the ship each year stands at 8 units and the number of employees at the shipyard is 13 at productivity value 61.53 percent, Sir Umar shipyard with a yearly boat productivity pf up to 4 units and a employees of a 5 with 80 percent of productivity and CV. KELING shipyard with the production of ships annually reaches 12 units and the number of 18 employees at 66.66 percent. At some shipyards that become research samples have a common thread in their management. Key word :CompartmentalizationProductivity, The Shipyard Industry